2015
DOI: 10.1089/neu.2014.3497
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Injury Causes Chronic Liver Pathology in Rats

Abstract: Traumatic spinal cord injury (SCI) causes major disruption to peripheral organ innervation and regulation. Relatively little work has investigated these post-SCI systemic changes, however, despite considerable evidence that multiple organ system dysfunction contributes to chronic impairments in health. Because metabolic dysfunction is common after SCI and the liver is a pivotal site for metabolic homeostasis, we sought to determine if liver pathology occurs as a result of SCI in a rat spinal contusion model. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 72 publications
2
73
1
Order By: Relevance
“…[30][31][32][33] In addition, a rat contusion model study found ALT to be significantly raised in the 21 days following injury, coupled with excess lipid accumulation and increased expression of pro-inflammatory genes. 34 Interestingly, this study also detected liver inflammation following lumbar SCI, 34 whereas previous studies in rats had shown that liver inflammation can occur within 30 min of SCI, 35 and that its severity correlates with level of injury. 31 AP, another analyte of the predictive ''liver function'' factor, is an enzyme that plays a significant role in bone mineralization, and has four isoenzymes, which are intestinal (IAP), placental (PLAP), germinal (GCAP), and tissue nonspecific (TNAP).…”
mentioning
confidence: 49%
“…[30][31][32][33] In addition, a rat contusion model study found ALT to be significantly raised in the 21 days following injury, coupled with excess lipid accumulation and increased expression of pro-inflammatory genes. 34 Interestingly, this study also detected liver inflammation following lumbar SCI, 34 whereas previous studies in rats had shown that liver inflammation can occur within 30 min of SCI, 35 and that its severity correlates with level of injury. 31 AP, another analyte of the predictive ''liver function'' factor, is an enzyme that plays a significant role in bone mineralization, and has four isoenzymes, which are intestinal (IAP), placental (PLAP), germinal (GCAP), and tissue nonspecific (TNAP).…”
mentioning
confidence: 49%
“…Compromised liver function may exacerbate the magnitude and effects of BT after SCI. Signs of liver disease (e.g., nonalcoholic steatohepatitis [NASH]) develop soon after SCI, and hepatic inflammation has been implicated as a key mediator of intraspinal inflammation (Campbell et al, 2008; Fleming et al, 2012; Anthony and Couch, 2014; Sauerbeck et al, 2015). Like the MLNs, the liver acts as a firewall, filtering gut microbes that drain from the intestine into the hepatic portal vein (Jenne and Kubes, 2013; Balmer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To determine effect of TAM on tumorigenesis, the liver was extracted after fixation at 35 DPI. 29 Also, the brain was dissected, and both organs were dried overnight and weighed 24 h after dissection. 30 …”
Section: Animal Sacrifice and Tissue Collectionmentioning
confidence: 99%